Local Wisdom in Designing ESP for Community-Based Tourism Practitioners: A Study of Needs Analysis - Lemmuela Alvita Kurniawati; Susanti Malasari (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2022)
The present study aimed to investigate the target needs as well as learning needs of the English for Specific Purposes (henceforth, ESP) training for community-based tourism (henceforth, CBT) practitioners in Meat village, North Sumatera and to investigate the integration of local wisdom in the design of the ESP training for CBT practitioners in Meat village, North Sumatera. Conducted by using mixed methods, this study was carried out involving six CBT practitioners in Meat village. A questionnaire and a focus group discussion were used to gather the data. The data were analyzed descriptively to provide a complete understanding of the research objectives. The findings of the study revealed that the target needs consisted of the participants’ necessities in the ESP training, the participants’ lacks, and the participants’ wants towards the ESP training. In addition to this, learning needs comprised of the content materials, teaching and learning activities, medium of instruction, and time preference of the ESP training. The findings also revealed that local wisdom integrated in the design of the ESP training motivated the participants in learning and was considered providing authentic as well as meaningful learning experiences. The findings of this study provided an implication for ESP material developers and a contribution to studies of ESP for CBT in Indonesian context.